An Analysis of Adverse Event Reporting in Balloon Sinus Procedures. - Prince, Anthony; Bhattacharyya, Neil (Otolaryngology-Head & Neck Surgery, 2016)
Objective: (1) Become familiar with reported adverse events related to balloon dilation of the paranasal sinus ostia. (2) Understand the sequelae occurring with these events.Study Design: Retrospective analysis of a prospective database.Setting: OpenFDA database.Subjects and Methods: The OpenFDA program website of the Food and Drug Administration was queried with the Application Program Interface query system for medical device adverse events involving balloon devices for the dilation of paranasal sinus ostia from January 2006 through December 2014. The raw data were then tabulated, with adverse events codified by event type, sinus involved, injury type, device malfunction, surgeon error, and qualitative data. Sequelae were also quantified.Results: In sum, 114 adverse events were identified. Patient injury was the most frequently reported adverse event (n = 72), followed by 36 device malfunctions, 4 deaths, and 2 unclassified. The most common injury involved orbital complications, including 23 (20.2%) orbital wall fractures and 22 (19.3%) postseptal and 22 (19.3%) preseptal orbital injuries. In addition, there were 17 (14.9%) skull base injuries and 7 (6.1%) cases of severe epistaxis observed; 11 (9.6%) cases mentioned surgeon error. Cerebrospinal fluid leak was significantly associated with frontal surgery (P = .002) and sphenoid surgery (P = .001), whereas post- and preseptal orbital injury was associated with maxillary surgery (P = .017 and P = .002). Epistaxis was associated with sphenoid surgery (P = .032).Conclusions: Based on the number of balloon sinus procedures performed, Food and Drug Administration-reported adverse events are uncommon, although a select portion can be severe. Surgeons should be aware of different complications reported with specific sinuses addressed with balloon techniques.